The effect of CO 2 ramping rate on the transient weakening of the Atlantic Meridional Overturning Circulation - Camille Hankel (Proceedings of the National Academy of Sciences, 2025)
The Atlantic Meridional Overturning Circulation (AMOC) is a key component of the global climate that is projected to weaken under future anthropogenic climate change. While many studies have investigated the AMOC’s response to different levels and types of forcing in climate models, relatively little attention has been paid to the AMOC’s sensitivity to the rate of forcing change, despite it also being highly uncertain in future emissions scenarios. In this study, I isolate the AMOC’s response to different rates of CO 2 increase in a state-of-the-art global climate model and find that the AMOC undergoes more severe weakening under faster rates of CO 2 change, even when the magnitude of CO 2 change is the same. I then propose an AMOC-ocean heat transport-sea ice feedback that enhances the decline of the circulation and explains the dependence on the rate of forcing change. The AMOC’s rate-sensitive behavior leads to qualitatively different climates (including differing Arctic sea ice evolution) at the same CO 2 concentration, highlighting how the rate of forcing change is itself a key driver of global climatic change.